Sex differences in leg dexterity are not present in elite athletes - Lawrence, E. L.; Peppoloni, L.; Valero-Cuevas, F. J. (Journal of Biomechanics, 2017)
We studied whether the time-varying forces that control unstable foot-ground interactions provide insight into the neural control of dynamic leg function. Twenty elite (10 F, 26.4 ± 3.5 yrs) and 20 recreational (10 F, 24.8 ± 2.4 yrs) athletes used an isolated leg to maximally compress a slender spring designed to buckle at low forces while seated. The foot forces during the compression at the edge of instability quantify the maximal sensorimotor ability to control dynamic foot-ground interactions. Using the nonlinear analysis technique of attractor reconstruction, we characterized the spatial (interquartile range IQR) and geometric (trajectory length TL, volume V, and sum of edge lengths SE) features of the dynamical behavior of those force time series. ANOVA confirmed the already published effect of sex, and a new effect of athletic ability, respectively, in TL (p = 0.014 and p < 0.001), IQR (p = 0.008 and p < 0.001), V (p = 0.034 and p = 0.002), and SE (p = 0.033 and p < 0.001). Further analysis revealed that, for recreational athletes, females exhibited weaker corrective actions and greater stochasticity than males as per their greater mean values of TL (p = 0.003), IQR (p = 0.018), V (p = 0.017), and SE (p = 0.025). Importantly, sex differences disappeared in elite athletes. These results provide an empirical link between sex, athletic ability, and nonlinear dynamical control. This is a first step in understanding the sensorimotor mechanisms for control of unstable foot-ground interactions. Given that females suffer a greater incidence of non-contact knee ligament injuries, these non-invasive and practical metrics of leg dexterity may be both indicators of athletic ability, and predictors of risk of injury.